2020
DOI: 10.1002/smi.2923
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events and adolescent well‐being: The role of parent and peer relationships

Abstract: It is well established that stressful life events (e.g., family bereavements or moving to a new country) are damaging to psychological health and well‐being. Indeed, social relationships are often noted as an important factor that can influence well‐being and buffer the negative effects of stress. However, the quality and source of these relationships, particularly for adolescents, are often overlooked. Using the Growing Up in Ireland Survey, a population‐based study of 13‐year‐old Irish adolescents (N = 7,525… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 75 publications
6
59
1
2
Order By: Relevance
“…Mínguez (2020) provided evidence for personal relationships being the strongest factor for predicting happiness according to the Subjective Wellbeing literature. One aspect leading to wellbeing is that peer relationships can buffer the negative effects of stress or fear (McMahon et al, 2020). For example, Baines and MacIntyre's (2019) research illustrated that enjoyment of sitting with peers to eat a meal was positively related to greater liking of lessons in school and school liking generally.…”
Section: Explainedmentioning
confidence: 99%
“…Mínguez (2020) provided evidence for personal relationships being the strongest factor for predicting happiness according to the Subjective Wellbeing literature. One aspect leading to wellbeing is that peer relationships can buffer the negative effects of stress or fear (McMahon et al, 2020). For example, Baines and MacIntyre's (2019) research illustrated that enjoyment of sitting with peers to eat a meal was positively related to greater liking of lessons in school and school liking generally.…”
Section: Explainedmentioning
confidence: 99%
“…During such times, where emotional balance can go for a toss, parent and peer relationships can matter a lot (McMahon et al, 2020). Further, there is a high chance of people developing psychological stress and disorders like depression, insomnia, anxiety, anger, boredom, etc.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…However, in addition to habits or lifestyles, there are social and psychological factors that contribute to young people’s well-being and therefore influence their HRQoL. Family relationships, for example, have been shown to be an important conditioning factor of adolescent well-being [ 19 , 20 , 21 , 22 ], relationships between parents [ 23 ], relationships with peers [ 19 , 24 ] or satisfaction with school [ 25 ]. For example, the study by Sánchez-Alcaraz showed significant correlations between all dimensions of HRQoL, with students with better self-esteem and better relationships with family, friends and school having a higher quality of life [ 26 ].…”
Section: Introductionmentioning
confidence: 99%